Use of zebrafish as a model to understand mechanisms of addiction and complex neurobehavioral phenotypes - Mathur, Priya (2010)
Despite massive research efforts the exact pathogenesis and pathophysiology of addiction and neuropsychiatric disorders such as anxiety, schizophrenia and autism remains largely unknown. Animal models can serve as tools to understand the etiology and pathogenesis of these disorders. In recent years researchers are turning to zebrafish as it allows easy access to all developmental stages and imaging of pathological processes as well as automated behavioral quantification coupled with large scale screening and mutagenesis strategies. This review summarizes studies conducted over the last few years which demonstrate the relevance of the zebrafish model to human diseases including addiction and neuropsychiatric disorders.